(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the genesis and origin of the image of Khoja in the poem “Hayratul abror ” from the cycle “Hamsa” by Alisher Navoi. In particular, the roots of the reconstruction of this image in the story “Tayr” by Avicenna and in the work “Kimyoi saodat” by Imam Gazzoli have been studied, as well as the interpretation of the works “Mahzanul asror” by Ganzhavi and “Matlail anvor ” by Khusraw Dehlavi , Navoi’s skill is revealed in the examples of comparative analysis.